2020
DOI: 10.1002/elps.202000123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dielectric gradients‐mediated ions partitioning on the electrophoresis of composite soft particles: An analytical theory

Abstract: In this work, we report original analytical expressions defining the electrophoretic mobility of composite soft particles comprising an inner core and a surrounding polymer shell with differentiated permeabilities to ions from aqueous background electrolyte and to fluid flow developed under applied DC field conditions. The existence of dielectric permittivity gradients operational at the core/shell and shell/solution interfaces is accounted for within the Debye-Hückel approximation and flat plate configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…The Brinkmann screening length of various core-shell structured bioparticles ranges up to 30 nm [19,20]. In addition, several studies have shown that the dielectric permittivity of peripheral polymeric membrane of such a particle can be significantly lower than that of the aqueous medium [31][32][33][34][35][36]53,54].…”
Section: Resultsmentioning
confidence: 99%
“…The Brinkmann screening length of various core-shell structured bioparticles ranges up to 30 nm [19,20]. In addition, several studies have shown that the dielectric permittivity of peripheral polymeric membrane of such a particle can be significantly lower than that of the aqueous medium [31][32][33][34][35][36]53,54].…”
Section: Resultsmentioning
confidence: 99%
“…Since polyelectrolyte layer and bulk electrolyte solution have distinct dielectric permittivity, the self-energies of an ion, W i , in the two regions differ from each other. The difference in self-energy of the ion causes ion partitioning, which can be quantified as ion partition coefficient [44,45,46,47,48,49,50]…”
Section: Theorymentioning
confidence: 99%
“…Ion partitioning effect modifies the charge density in polyelectrolyte layer and consequently affects the electrophoresis of soft charged particles as well as electrokinetics in soft nanochannels. Very recently, ion partitioning effect attracted a great deal of interest of researchers studying the electrophoresis of charged soft particles immersed in electrolytes [44,45,46,47,48,49,50] and electrokinetic transport in soft nanochannels [51,52,53]. The analytical and numerical studies [44,49,50,45,46,47,48],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of ion partitioning on the electrokinetics in soft nanochannels were analyzed in order to offset the existing work results with the consideration of equal permittivity inside and outside the ECL [22]. A large number of articles dealt with such effects in various research studies [23][24][25]. In this paper, however, we have not added the ion partitioning effect to present thruster systems since this consideration is repetitive.…”
Section: Introductionmentioning
confidence: 99%